Diagnóstico da fauna (aves, répteis, anfíbios e mamíferos) do município de Araraquara, São Paulo, Brasil, como subsídio para conservação e o manejo da diversidade - Barbosa, João Henrique (Universidade Federal de São Carlos, 2020)
The fragmentation and loss of habitats in the interior of the state of Sao Paulo in the last 50 years is probably the greatest threat to wildlife. In addition, only 1.5% of these fragments have data on their biodiversity. The objective of this work was to systematize and diagnose the fauna situation in the municipality of Araraquara-SP and to produce educational and informative material on the fauna of Araraquara-SP. The databases of the work performed by the city's environmental sectors in the period from 2013 to 2019 were used. Through them, there was an increase in the number of calls to wild animals in the urban environment, from 49 calls in 2013 to 418 in 2019. It was possible to identify a concentration of cases between September and February (72% to 85% of cases), the rainiest months of the year having a direct relationship with the reproductive period of the species. In 62% of the cases attended, rescue action was required, where 78% was immediately released; 17% referred to veterinary clinics and zoos; and 5% died, whose causes vary: being run over (54%); attack by domestic animals (22%); shock with panes of glasses (10%); direct or indirect poisoning (5%); and unknown causes (9%). In the other 38% of the consultations, guidance and awareness were provided. Among the rescued species, there is a predominance of Didelphis albiventris what can be inferred to be an early synanthropy process. A list was made up of 274 species of birds, 60 mammals, 34 reptiles, and 17 amphibians distributed in 38 orders and 104 families, of these 62 are threatened at the state level, 6 nationally, 9 by IUCN, and 83 in CITES appendices. With this information, 4000 units of the booklet entitled “Fauna de Araraquara” were made with a list of species, 60 photographs, texts about the municipality, and maps of the sampled areas. It was printed by the municipality and launched on June 5, 2019, in celebration of World Environment Day. It was delivered to all public schools in Araraquara and the region as well as being made available online to the entire population. The next steps are to maintain field collections with biannual publications, including other groups such as the ichthyofauna and invertebrates that were not included in this study, and to evaluate the use of the booklet as an instrument of environmental education.
Diagnosis of fauna (birds, reptiles, amphibians and mammals) in the municipality of Araraquara, São Paulo, Brazil, as a subsidy for conservation and management of diversity
Keywords: Conservação da fauna; Cartilha; Lista de espécies; Fauna conservation; Booklet; List of species; CIENCIAS BIOLOGICAS::ZOOLOGIA